Retinal nerve fiber layer, macular thickness and anterior segment measurements in attention deficit and hyperactivity disorder - Taha Ayyildiz; Didem Ayyildiz (Psychiatry and Clinical Psychopharmacology, 2019)
AIM: We aimed to explore whether there is difference in terms of Retinal Nerve Fiber Layer (RNFL) thickness, macula thickness and anterior segment structures of the eye between children and adolescents with ADHD and healthy controls. METHOD: Children and adolescents aged 8–16 years who were admitted to the Child Psychiatry outpatient clinic of Ahi Evran University Hospital diagnosed with ADHD constituted the study group. Exclusion criteria included patients who had any systemic/ocular or psychiatric disorder other than ADHD and patients who had any psychopharmacological treatment. Participants in the control group were children and adolescents who applied to the outpatient clinic of Ophthalmology at the same hospital with no chronic medical or psychiatric disorder. Groups were compared in terms of central macular thickness, retinal nerve fibre layer thickness (RNFL), central corneal thickness, corneal diameter, mean corneal radius of curvature, anterior chamber depth, and axial length using Optical Coherence Tomography (OCT) and Optical Biometry. RESULTS: Data obtained from the measurements of 60 eyes of 30 patients with ADHD and 60 eyes of 30 patients of the control group were evaluated. Groups were similar in terms of age and gender. Corneal thickness (p = 0.001) and axial length (p = 0.04) values were significantly higher in ADHD group while the mean corneal curvature radius (p = 0.03) was significantly lower in ADHD group than in controls. No significant difference was observed between groups in terms of RNFL thickness, macular thickness, the corneal diameter, and anterior chamber depth measurements. CONCLUSION: In recent years, the use of OCT in neuropsychiatric diseases has increased the interest in identifying possible biomarkers and the elucidation of neurodegenerative and neurodevelopmental mechanisms that contribute to the nature of these diseases. Differences in the ophthalmic anatomical structures observed between healthy controls and cases with ADHD, which is a neurodevelopmental disorder, need to be supported by longitudinal studies with a larger sample and using OCT in connection with brain imaging.